Analgesic Prescribing Trends of Opioids, Nonsteroidal Anti-Inflammatory Drugs, and Paracetamol in Taiwan (2001‐2020): Age-Period-Cohort Cross-Sectional Study - Chun-Ji Lin; Chia-Shuan Chang; Chih-Yi Wu; Jiun-Yi Wang; I-Ching Lin; Hung-Yi Chiou (JMIR Public Health and Surveillance, 2026)
Abstract Background Despite ongoing global changes in analgesic prescribing practices, long-term trends accounting for age, period, and cohort effects remain poorly understood in Asian populations, where opioid and nonopioid prescribing trajectories differ from those observed in Western nations. Objective This study aimed to examine the long-term prescribing trends of opioids, nonsteroidal anti-inflammatory drugs (NSAIDs), and paracetamol in Taiwan by age, calendar period, and birth cohort using an age-period-cohort (APC) framework. Methods We conducted a population-based repeated cross-sectional study using Taiwan National Health Insurance claims data (2001‐2020). The cohort included all insured individuals aged 1 to 85 years, with an annual population size of 22.3 to 23.1 million. Exposure variables were structured for APC modeling, comprising 5-year age groups, four 5-year calendar periods (2001‐2020), and 5-year birth cohorts (1920‐1924 to 2015‐2019). Results Opioid prescribing prevalence escalated from 123.66 per 100,000 persons in 2001 to 2005 to 706.93 in 2016 to 2020. APC analysis showed a significant positive net drift for opioids (+10.93% per year, 95% CI 10.36%-11.51%; P